Characterization of phycobilisome glycoproteins in the cyanobacterium Anacystis nidulans R2. - Riethman, H C (1988)
Concanavalin A-reactive linker and anchor subunits of phycobilisomes from Anacystis nidulans R2 (H. C. Riethman, T. P. Mawhinney, and L. A. Sherman, FEBS Lett. 215:209-214, 1987) were purified electrophoretically and analyzed for carbohydrate composition and quantity. Different quantities of glucose and N-acetylgalactosamine were found on the concanavalin A-reactive subunits analyzed. Proteolytic analysis of the purified subunits suggested that small regions of the 33- and 27-kilodalton linker polypeptides previously shown to be important for in vitro phycobilisome assembly contained the concanavalin A-reactive carbohydrates present on these subunits. The linker and anchor subunits from the morphologically different phycobilisome of Synechocystis sp. strain PCC6714 were also shown to be concanavalin A reactive. Membranes from iron-starved Anacystis nidulans, which lack assembled phycobilisomes and are associated with glycogen deposits, were shown to be depleted of linker and anchor proteins and to accumulate very large quantities of a concanavalin A-reactive, extrinsic membrane glycoprotein. We suggest that this iron stress-induced glycoprotein is associated with the glycogen deposits on the thylakoid surface and that the glycosylation of phycobilisome linker and anchor subunits is involved in the physiological regulation of phycobilisome assembly and degradation.